2022
DOI: 10.1080/22221751.2022.2155251
|View full text |Cite
|
Sign up to set email alerts
|

Antibody persistence and safety after heterologous boosting with orally aerosolised Ad5-nCoV in individuals primed with two-dose CoronaVac previously: 12-month analyses of a randomized controlled trial

Abstract: Antibody persistence and safety up to 12 months of heterologous orally administered adenovirus type-5 vector-based COVID-19 vaccine (Ad5-nCoV) in individuals who were primed with two-dose inactivated SARS-CoV-2 vaccine (CoronaVac) previously, has not been reported yet. This randomized, open-label, single-centre trial included Chinese adults who have received two-dose CoronaVac randomized to low-dose or high-dose aerosolised Ad5-nCoV group, or CoronaVac group. In this report, we mainly evaluated the geometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The orally aerosolized Ad5-nCoV is supposed to be able to elicit respiratory mucosal immunity such as secretory IgA, which would play an important role in preventing viral transmission. These results confirmed that heterologous boosting is more effective in eliciting NAb responses than the homologous boosting regimen [ 6 ].…”
supporting
confidence: 73%
“…The orally aerosolized Ad5-nCoV is supposed to be able to elicit respiratory mucosal immunity such as secretory IgA, which would play an important role in preventing viral transmission. These results confirmed that heterologous boosting is more effective in eliciting NAb responses than the homologous boosting regimen [ 6 ].…”
supporting
confidence: 73%
“…Two nasally delivered, adenoviral-vectored COVID-19 vaccines (iNCOVACC (chimpanzee adenoviral (ChAd)-SARS-CoV-2-S) and Convidecia Air (human Ad5-nCoV-inhaled)) targeting the S protein of the Wuhan-1 strain were approved in late 2022 in India and China, respectively, for use as primary or booster immunizations. Nonetheless, data on the efficacy of these nasally delivered vaccines against transmission 22 , 23 or circulating antigen-shifted Omicron strains are absent.…”
Section: Mainmentioning
confidence: 99%
“…Full-text screening was performed for 20 articles, of which 5 articles did not meet the eligibility criteria and were excluded. A total of 15 studies [18][19][20][32][33][34][35][36][37][38][39][40][41][42][43] (11 analyzing safety, 13 analyzing immunogenicity, and 3 analyzing effective) were found to meet the inclusion criteria and were included in the systematic review and meta-analysis. The PRISMA flowchart depicted the process of article screening and selection (Figure 1).…”
Section: The Search Resultsmentioning
confidence: 99%
“…Data are available online for the included studies. [18][19][20][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%